1988
DOI: 10.1002/jor.1100060417
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic release from an experimental biodegradable bone cement

Abstract: An experimental biodegradable bone cement [poly(propylene fumarate)-methylmethacrylate] (PPF-MMA) has been compared in vivo with polymethylmethacrylate (PMMA) as a carrier agent for local release of antibiotics. This approach is potentially applicable to the treatment of chronic osteomyelitis where the clinical goal is to achieve sustained high concentrations of antibiotics locally in the infected bone. In our experiments, gentamicin- and vancomycin-impregnated cylindrical PMMA and PPF-MMA cement specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 27 publications
0
42
0
4
Order By: Relevance
“…Meyer et al [30] prepared biodegradable beads from poly-( L )-lactide, in which the gentamicin molecule is stabilized with hydrophilic ion pairs. Other authors also reported on promising experimental data obtained with biodegradable carriers like hydroxyapatite, tricalcium phosphate [31] , polycaprolactone [32] and poly(propylene fumarate)-methylmetacrylate in vivo in rats [33] . Recently, vancomycin-containing hydroxyapatite blocks were implanted into 5 patients suffering from osteomyelitis induced by methycillin-resistant S. aureus [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Meyer et al [30] prepared biodegradable beads from poly-( L )-lactide, in which the gentamicin molecule is stabilized with hydrophilic ion pairs. Other authors also reported on promising experimental data obtained with biodegradable carriers like hydroxyapatite, tricalcium phosphate [31] , polycaprolactone [32] and poly(propylene fumarate)-methylmetacrylate in vivo in rats [33] . Recently, vancomycin-containing hydroxyapatite blocks were implanted into 5 patients suffering from osteomyelitis induced by methycillin-resistant S. aureus [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Although effective in inhibiting bacterial growth and biofilm formation, several of the implant coating strategies have the limitation of requiring prefabrication [25,43] and chemical modification with specific preselected antibiotics [4,29]. Release of antibiotic resembles the burst release observed in commonly used polymethylmethacrylate (PMMA) and calcium sulfate drug delivery matrices [23,47]. Unlike PMMA, which requires secondary removal through surgical procedures, phosphatidylcholine coatings are degradable and materials have been used in orthopaedic applications [26].…”
Section: Discussionmentioning
confidence: 99%
“…Scanning electron microscopy images of biofilm formation on implants resembled images from similar retrieved infected implants [10,52] with rounded S aureus and rod-shaped P aeruginosa colonies visible in untreated groups. Formation of fibrous tissue, to varying degrees, along the outer portion of the wire exposed to soft tissue was seen with morphology that may be indicative of fibroblast or macrophage infiltration [3,23,36]. Material properties of the coating may have contributed to this response [26,77]; however, the majority of the fibrous tissue was formed at the point of the wire that curved and extended from the catheter, which may have been a location for rubbing and irritation as the animals moved or were groomed.…”
Section: Discussionmentioning
confidence: 99%
“…They found that during 4 months, more than 60% of the total antibiotic content is continuously released from these beads. Gerhardt et al [15] compared gentamycin and vancomycin release from experimental biodegradable bone cement, poly-(propylene-fumarate)-methylmethacrylate and PMMA in vivo in rats. Antibiotic concentrations of the blood and the wound secretion were determined with immunoassay and microbiological agar diffusion techniques.…”
Section: Discussionmentioning
confidence: 99%